Developing a framework and algorithm for scalability to evaluate the performance and throughput of CRM systems. Issue 1 (2nd January 2017) - Altalhi, Abdulrahman H.; AL-Malaise AL-Ghamdi, Abdullah; Ullah, Zahid; Saleem, Farrukh
Abstract: Scalability in hardware and/or software is an important factor for enhancing the performance of running processes as well as the throughput of the system of business organizations. This paper explores the need for scalability and issues related to extending the resources in order to ensure an improved and scaled-up Customer Relationship Management (CRM) architecture. The main contribution discussed in this paper is the proposal of a conceptual framework for measuring the process performance and throughput of the system beyond the selection of the type of scalability. Furthermore, this paper concerns the CRM system, as customer requests, their online transactions, and responses need a fast and efficient system. Taking into consideration all these factors, ultimately this paper proposed a customer-friendly framework for measuring the process performance and throughput of the system. Finally, the proposed framework's steps are shown in an algorithm calculating process performance and throughput of the system.